ABC proteins and antibiotic drug resistance: is it all about transport?. (26th October 2005) - Kerr, I.D.; Reynolds, E.D.; Cove, J.H.
Abstract : The precise mechanism of antibiotic-resistance-conferring ABC (ATP-binding-cassette) proteins (termed NBD2 ) remains open to debate. Currently, two hypotheses are recognized. In one, the NBD2 proteins are envisaged to act at the ribosome to impair antibiotic access to the target site on the 23 S rRNA. In the other, NBD2 proteins are believed to act as the components of ATP driven efflux pumps by associating with membrane spanning proteins capable of binding and transporting antibiotics. Pertinent data in support of these two hypotheses are discussed in this paper.